Global warming and financial umbrellas - Cesare Dosi; Michele Moretto (Fondazione Eni Enrico Mattei (FEEM), 2001)
A new instrument for hedging weather risks has made its appearance in the financial arena. Trade in 'weather derivatives' has taken off in the US, and interest is growing elsewhere. Whilst such contracts may be simply interpreted as a new tool for solving a historical problem, the question addressed in this paper is if, besides other factors, the appearance of weather derivatives is somehow related to anthropogenic climate change. Our tentative answer is positive. Since 'global warming' does not simply mean an increase in averaged temperatures, but increased climate variability, and increased frequency and magnitude of weather extremes, derivative contracts may potentially become a useful tool for hedging some weather risks, insofar as they may provide coverage at a lower cost than standard insurance schemes.
Keywords: G10; Q20; 330; Global warming; climate variability; insurance coverage; weather derivatives; Derivat; Klimawandel; Versicherungsökonomik; Theorie; Wetter